2017
DOI: 10.1111/hae.13318
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide synovectomy/synoviorthesis (RS) in patients with bleeding disorders: A review of patient and procedure demographics and functional outcomes in the ATHNdataset

Abstract: Right-sided joint procedures were more prevalent than left-sided procedures. Overall, case-patients had worse joint ROM compared to control-patients and published normative values. Geographically, there was regional variation in RS utilization, as the Southeast region had the largest percent of case-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Since 1970s, multiple studies have demonstrated the effectiveness of radioactive synovectomy utilizing various agents such as gold‐198 (198Au), yttrium‐90 (90Y), rhenium‐186 (186Re) and chromic phosphate‐32 (32P) …”
Section: Introductionmentioning
confidence: 99%
“…Since 1970s, multiple studies have demonstrated the effectiveness of radioactive synovectomy utilizing various agents such as gold‐198 (198Au), yttrium‐90 (90Y), rhenium‐186 (186Re) and chromic phosphate‐32 (32P) …”
Section: Introductionmentioning
confidence: 99%
“…Radioisotope synovectomy using a pure beta emitter (phosphorus‐32, yttrium‐90, and rhenium) is highly effective, has few side effects, and can be accomplished in a single outpatient procedure. 78 , 79 , 80 , 81 , 82 …”
Section: Resultsmentioning
confidence: 99%
“…[75][76][77] Radioisotope synovectomy using a pure beta emitter (phosphorus-32, yttrium-90, and rhenium) is highly effective, has few side effects, and can be accomplished in a single outpatient procedure. [78][79][80][81][82] However, limitations due to radionuclide availability and fear of potential related risk (seldom reported) should be considered. In addition, although synovectomy/synoviorthesis is known to reduce synovitis and, in turn, the frequency of bleeding episodes, no evidence about specific effects on articular degeneration are known.…”
Section: Role Of Orthopaedic Surgery (Table Iv)mentioning
confidence: 99%
“…Several approaches for synovial ablation are described. Radioactive or chemical synovial ablation is effective and require minimal CFC prophylaxis compared to classical open or arthroscopic synovectomy . Another procedure is angiographic embolization of synovial arteries which also needs minimal CFC prophylaxis .…”
Section: Haemostatic Surgical Proceduresmentioning
confidence: 99%